Identifying the physicochemical properties of β-cyclodextrin polymers that determine the adsorption of perfluoroalkyl acids. (1st February 2022) - Ching, Casey; Ling, Yuhan; Trang, Brittany; Klemes, Max; Xiao, Leilei; Yang, Anna; Barin, Gokhan; Dichtel, William R.; Helbling, Damian E.
Highlights: Studied perfluoroalkyl acid (PFAA) removal from water by 34 cyclodextrin polymers. Polymer surface charge is important regardless of PFAA chain length and head group. Polymer porosity, surface area, and size are important for adsorption kinetics. Crosslinker content is important for adsorption of short-chain PFAAs like PFBA. Crosslinker hydrophobicity is important for adsorption of long-chain PFAAs. Abstract: Cyclodextrin polymers (CDPs) are emerging adsorbents with demonstrated potential to remove perfluoroalkyl acids (PFAAs) from water. However, little is known about how the physicochemical properties of different types of CDPs determine PFAA adsorption on CDPs. In this study, we investigated the adsorption performance of 34 CDPs which consist of 14 different crosslinkers and exhibit a wide range of physicochemical properties. The performance metrics included adsorption kinetics, equilibrium adsorption density, and adsorption affinity for six PFAAs. We then used complementary bivariate and multivariate analyses to discover relationships between sixteen measurable physicochemical properties of the CDPs and their performance as adsorbents. We found that: (1) CDPs with a less negative or more positive surface charge will exhibit enhanced adsorption of all types of PFAAs; (2) CDPs with greater porosity and surface area will exhibit enhanced adsorption kinetics for all types of PFAAs; (3) CDPs with greater crosslinker content will exhibit enhanced adsorption of short-chain PFAAs; (4) CDPs containing more hydrophobic crosslinkers will exhibit enhanced equilibrium adsorption density and adsorption affinity for longer-chain PFAAs; and (5) CDPs with smaller particle sizes will exhibit enhanced adsorption kinetics and equilibrium adsorption density for all PFAAs. These insights will enable the further development of CDPs and other novel adsorbents to optimize their performance for removing PFAAs during water and wastewater treatment or groundwater remediation.